2014
DOI: 10.1007/978-3-319-11973-1_22
|View full text |Cite
|
Sign up to set email alerts
|

A Sociological Contribution to Understanding the Use of Robots in Schools: The Thymio Robot

Abstract: Abstract. The Thymio II robot was designed to be used by teachers in their classrooms for a wide range of activities and at all levels of the curriculum, from very young children to the end of high school. Although the educationally oriented design of this innovative robot was successful and made it possible to distribute more than 800 Thymio robots in schools with a large majority in the French-speaking part of Switzerland, it was not sufficient to significantly raise the number of teachers using robot techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
1
15
0
3
Order By: Relevance
“…Based on our study, we identified two important issues which require our attention: (1) standardization of evaluation techniques which are used to quantify robot-based learning: merging statistical analysis, surveys and interviews and (2) development of tailored robot-based pedagogical modules assisting traditional K-12 curricula and associated teacher training programs [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our study, we identified two important issues which require our attention: (1) standardization of evaluation techniques which are used to quantify robot-based learning: merging statistical analysis, surveys and interviews and (2) development of tailored robot-based pedagogical modules assisting traditional K-12 curricula and associated teacher training programs [86].…”
Section: Discussionmentioning
confidence: 99%
“…Such comfortability can only be achieved through proper training and active/pro-active involvement. Many of the teachers are hesitant in dealing with robotics, such behavior does not reflect their unwillingness to learn new concepts, sometimes it can be associated to the lack of standard curricula, and the affiliated long term benefit [86]. These limitations can be minimized by developing standardized and proven stable long-term curricula and related teacher training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Note that we did not consider amotivation, which is "the state of lacking an intention to act" [19]. As Kradolfer showed [10], it is difficult to find teachers who are explicitly amotivated. Moreover, our pool of respondents displayed their motivation by subscribing to the training sessions.…”
Section: Methodsmentioning
confidence: 98%
“…This study, which looked at elementary, middle, and high school teachers, still lacked a more detailed analysis of the specific motivation behind this choice. Kradolfer et al [10] conducted a deeper analysis, using sociological methods to understand the blocking factors in the use of robots by teachers who were already familiar with this technology. They came to the conclusion that such limitations could be a result of the high price of robots, the absence of either institutional injunctions or pedagogical research in educational robotics, or the scarcity of appropriate materials and teacher training.…”
mentioning
confidence: 99%
“…Our main concern during the mechatronic design of Thymio was to keep a low production cost. Price is a key factor for the adoption of the robot by schools [17]. In our previous experience with designing robots, most of the costs were due to the electronics and the sensors [18], not to the mechanical parts.…”
Section: A Low Pricementioning
confidence: 99%